The Contests of the Rural Landscape and the Expansion of Urban Spot in Costa Rica (1973-2003) - Zavaleta Ochoa, Eugenia (2018)
The so-called Rural Landscape Contests and some Urban Landscape Contests, which were organized by state institutions, were held between 1973 and 2003. The goal of this paper is to determine the reasons that had official instances to restart and encourage again the theme of the rural landscape, which had had a preponderance in the decade of 1930. Newspapers of the time and archives of the Costa Rican Art Museum and the Ministry of Culture, Youth and Sports were consulted. It was also important to conduct interviews with organizers, artists and juries who participated in these competitions. In light of these sources, on one hand, it was established that the State had become an urbanizing agent and, on the other hand, it was clinging to a visual art representation of the nation: the rural landscape.